2001
DOI: 10.2307/1223889
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Phylica L. (Rhamnaceae) with an emphasis on island species: evidence from plastid trnL‐F and nuclear internal transcribed spacer (ribosomal) DNA sequences

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . International Association for Plant Taxonomy (IAPT) is collaborating with JSTOR to digitize, preserve and extend access to Taxon. Chase, M. W.: Phylogenetic analysis of Phyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 40 publications
4
26
0
Order By: Relevance
“…Only patterns in uniparentally inherited genomes might be expected to still exhibit evidence of paraphyly. In the DNA sequence analysis of plastid trnL-F (Richardson et al 2001a), there was weak evidence for paraphyly of P. paniculata, but this might also be due to differential inheritance of ancestral polymorphisms. Further study is required to better document this scenario.…”
Section: Origins Of the Island Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only patterns in uniparentally inherited genomes might be expected to still exhibit evidence of paraphyly. In the DNA sequence analysis of plastid trnL-F (Richardson et al 2001a), there was weak evidence for paraphyly of P. paniculata, but this might also be due to differential inheritance of ancestral polymorphisms. Further study is required to better document this scenario.…”
Section: Origins Of the Island Populationsmentioning
confidence: 99%
“…No fresh or silica-gel dried material of this species was available, and so it was not included in this study, but a trnL-F sequence derived from DNA extracted from herbarium material indicated that it was part of the island group (Richardson et al 2001a). Efforts to use the DNA extracted from herbarium material to produce an AFLP profile for this species were unsuccessful.…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The species may have dispersed from Gough to Ile Amsterdam as recently as 0.5 million years ago, and birds are the most plausible vector. [9] Rather similarly, mitochondrial DNA sequence data for subunit I of cytochrome oxidase has been used to create a phylogenetic tree for the mollusc genus Balea, including five species endemic to the Tristan-Gough group. It seems clear not only that the Tristan-Gough species arose from a single ancestor, but that ancestor shared an ancestral stock with a cluster of species in the Azores and Madeira, the Azorean ancestor itself being derived from Palaearctic stock.…”
Section: The Man Behind the Festschriftmentioning
confidence: 99%
“…The Cape flora of South Africa has always been of special interest to botanists and, over the past decade, has been the subject of studies focussing on (phylogenetic) patterns and processes underlying the species-level radiations mentioned above (e.g., Johnson, 1996;Johnson & al., 1998;Bakker & al., 1999b;Richardson & al., 2001;Goldblatt & al., 2002). Of special interest is whether these radiations occurred simultaneously, perhaps in a concerted response to a changing environmental or climatic factor.…”
Section: Introductionmentioning
confidence: 99%